2018
DOI: 10.3390/f9040221
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Ailanthus altissima and Native Robinia pseudoacacia in Early Succession: Implications for Forest Management

Abstract: Abstract:The goal of this study was to discover the nature and intensity of the interaction between an exotic invader Ailanthus altissima (Mill.) Swingle and its coexisting native Robinia pseudoacacia L. and consider management implications. The study occurred in the Mid-Appalachian region of the eastern United States. Ailanthus altissima can have a strong negative influence on community diversity and succession due to its allelopathic nature while R. pseudoacacia can have a positive effect on community divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This pattern was evident in our study, but as noted earlier, some of the invasive species present in the blowdowns that we studied had characteristics of late‐successional species, such as shade‐tolerance, which may allow them to persist as succession progresses (Martin et al, ). The expected trajectory of succession may not be the case in our study area since successional patterns can be altered by both windstorms (Holzmueller, Gibson, & Suchecki, ; Rich, Frelich, & Reich, ) and invasive species (Flory & Clay, ; Nilsen, Huebner, Carr, & Bao, ). Additionally, our study only covers 12 years of secondary succession progress.…”
Section: Discussionmentioning
confidence: 88%
“…This pattern was evident in our study, but as noted earlier, some of the invasive species present in the blowdowns that we studied had characteristics of late‐successional species, such as shade‐tolerance, which may allow them to persist as succession progresses (Martin et al, ). The expected trajectory of succession may not be the case in our study area since successional patterns can be altered by both windstorms (Holzmueller, Gibson, & Suchecki, ; Rich, Frelich, & Reich, ) and invasive species (Flory & Clay, ; Nilsen, Huebner, Carr, & Bao, ). Additionally, our study only covers 12 years of secondary succession progress.…”
Section: Discussionmentioning
confidence: 88%
“…Examples of direct facilitative interactions of native species on non‐natives in abiotically harsh and low‐productivity environments are common (examples above), but there are examples from more productive environments (e.g. Nilsen et al., 2018; Saccone et al., 2010; Von Holle, 2005). For instance, the North American Acer negundo has invaded the Middle Rhone floodplains forest of France where it reaches much higher densities than in its native range (Reinhart & Callaway, 2004).…”
Section: Native Species Directly Facilitating Non‐native Species (I)mentioning
confidence: 99%
“…Recently, in highly productive temperate forests of North America, Nilsen et al. (2018) found that the highly invasive Eurasian species Ailanthus altissima , performed much better when experimentally planted with the native Robinia pseudoacacia than when in monoculture.…”
Section: Native Species Directly Facilitating Non‐native Species (I)mentioning
confidence: 99%
“…Pioneer tree species plays a key role in the recovery of tree biomass C, for example, pine stands sequestered the highest amount of biomass C in the Midwestern and Appalachian coalfields, followed by hardwood and mixed stands [3]. Except for the pioneer tree or reclamation pattern, other factors also affected the accumulation of C, such as harvesting, fire and climate change [15][16][17][18], among which, competition for resources (e.g., nutrient, light) could be another important indicator [19][20][21][22][23]. It was deduced that the competition among trees was more fiercely in nutrient-lacking reclaimed dumps, because soil nutrient played an important role in tree's development and nutrient-depletion soil exacerbated the scarcity of resource [24,25].…”
Section: Introductionmentioning
confidence: 99%